Perforated Meckel's diverticulum causing in utero small bowel obstruction - Justin Faulkner; Rebecca Purvis; Imelda Odibo; Jeff Dehmer (Elsevier, 2021)
Meckel's diverticulum is a congenital anomaly involving a true diverticulum of the ileum. These diverticula can present in a variety of ways. They can be asymptomatic and discovered incidentally or can present with symptoms of infection, bleeding or obstruction. Typically, patients present around age 2. We present a case of an in utero perforation of a Meckel's diverticulum causing a small bowel obstruction diagnosed on prenatal imaging.